Synthesis and Properties of a Debonded Polycarboxylic Acid Superplasticizer. Issue 1 (October 2020) - Li, Guangzhou; Xiong, Qiumin; Chen, Xiaobin; Guan, Jican; Dang, Wei
Abstract: High-strength concrete has always had the problem of high viscosity which is not easy to construct, but reducing viscosity will inevitably affect the strength of concrete. In this paper, a kind of polycarboxylic acid series viscosity reducing agent JN-1 was synthesized by adjusting the synthetic raw material, which can reduce the viscosity and ensure the strength of high strength concrete for 28 days to reach or exceed 100%, Synthesis Key points are the use of acrylamide and the control side chain length.